PERAN KELOMPOK WANITA TANI HIJAU DALAM PEMANFAATAN PEKARANGAN RUMAH DI KELURAHAN ANAWAI KECAMATAN WUA-WUA KOTA KENDARI - Arnisa, Arnisa; Mappasomba, Musadar; Arimbawa, Putu; Batoa, Hartina (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The utilization of yards by Women Farmers Groups is imperative for ensuring food security; however, the efficacy of this practice is contingent upon the optimal functioning of the group, which, in practice, continues to grapple with numerous impediments. The objective of this study is to analyze the role of the Green Women Farmers Group in utilizing yards in Anawai Village, Wua-Wua District, Kendari City. The research population consists of all 30 members of the Green Women Farmers Group. The sample was determined using the census method. The present study employed a quantitative approach. The data presented herein were collected through a variety of research methods, including surveys, in-depth interviews, and a meticulous review of relevant documentation. The research variables of interest were the role of farmer groups and the utilization of home gardens. The collected data were then subjected to analysis using quantitative descriptive methods. The findings indicated that the Green Women Farmers Group (KWT) in Anawai Village, Wua-Wua District, Kendari City, exhibited a high level of proficiency in the utilization of yards, particularly in its functions as a learning class, a conduit for cooperation, and a production unit. Conversely, the level of yard utilization by its members was found to be moderate, contingent on the diversity of commodities produced and the ensuing benefits obtained. A correlation analysis reveals a robust and statistically significant positive association between group role and yard utilization (r = 0.774; p < 0.05). This finding suggests that effective group function implementation is associated with enhanced yard management and productivity among its members. Women's farmer groups have been shown to make a significant contribution to enhancing the effectiveness of yard management and fostering more productive and sustainable use of local resources.